Duration mismatch negativity in high-risk populations for schizophrenia - Pantlin, Lara N., author; Davalos, Deana, advisor; Malcolm, Matthew, committee member; Volbrecht, Vicki, committee member (Colorado State University. Libraries, 2016)
Schizophrenia is a potentially disabling and intractable disorder that is categorized by disturbances in sensory information processing and a psychotic episode. Recent research has targeted clinically high-risk populations and used mismatch negativity (MMN) as an identification tool to provide information regarding the onset of psychosis. Patients with schizophrenia have smaller MMNs compared to controls; thus reduced amplitudes may reflect physiological deficits in temporal perception. The present study evaluated differences in duration MMN (dMMN) amplitudes between healthy and potentially high-risk participants. The hypothesis was that the participants who met the criteria for high-risk according to the 16-item Prodromal Questionnaire (PQ) (score > 6) would have attenuated dMMN amplitudes compared to controls. Participants completed the PQ. Brain activity was recorded using EEG while participants were presented with 2880 samples (120 cycles of 24 samples) of randomized tones that differed in duration (Standard = 500 ms; Deviant 1 = 425 ms; Deviant 2 = 250 ms). Three analyses were applied (Analysis 1: Controls = 0; Analysis 2: Traditional cut-off score Controls < 6; Analysis 3: Simple linear regressions). T-tests at each electrode location did not yield significance for Deviant 1. Deviant 2 demonstrated significant trends in Analysis 2 (Fz: t(115) = -2.26, p = .01; Cz: t(115) = -2.11, p = .02). Analysis 3 demonstrated a significant negative, linear relationship between survey scores and MMN amplitudes (Fz: R2= .034, p = .047). Findings may provide a tool for identifying those who are considered high-functioning, but could develop psychosis or cognitive and psychological difficulties associated with psychosis.